2016
DOI: 10.1614/wt-d-15-00182.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Timing and Frequency of Flame Cultivation for Dewberry Control

Abstract: Flame cultivation (FC) uses brief exposures of high temperature to control weeds. Three sites in southeastern Massachusetts with dewberry present were studied over a 2-yr period to determine if seasonal timing and frequency of exposure to FC would reduce dewberry stem length and biomass, both in the year of and the year following treatment, and also to evaluate whether FC treatments altered the ratio (sugar : starch) of nonstructural carbohydrates (NSC) in dewberry roots. Dewberry plants were treated with a 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Box 577, West Highway 4, LaCrosse, KS, USA, 67548) at 1.2 km ha −1 and 345 kPa operating pressure utilizing 382 L/ha (192 kg ha −1 ) propane. The flame equipment utilized in this experiment used substantially more propane compared to others reported in the literature [31][32][33][34]. Since weather and solar radiation attributes affects cover crop biomass and solarization potential, average daily temperature, precipitation, and solar radiation are reported for each year in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Box 577, West Highway 4, LaCrosse, KS, USA, 67548) at 1.2 km ha −1 and 345 kPa operating pressure utilizing 382 L/ha (192 kg ha −1 ) propane. The flame equipment utilized in this experiment used substantially more propane compared to others reported in the literature [31][32][33][34]. Since weather and solar radiation attributes affects cover crop biomass and solarization potential, average daily temperature, precipitation, and solar radiation are reported for each year in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…However, these products following cover crop injury due to rolling/crimping may increase the cover crop termination rate, thus conserving soil moisture and facilitating earlier subsequent crop planting opportunities. Flame weeding has been evaluated for weed control before crop emergence or inter-row for onion, sweet corn, and cabbage (Brassica oleracea L.) [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the target weeds can be controlled with glyphosate, but FC can be less expensive and used in organic situations, and cranberry vines can recover from treatment with FC, whereas glyphosate treatments are often lethal [81]. Biomass collected in the year after treatment showed that two exposures of 9 s with an OF torch were more effective at reducing dewberry total, shoot, and root biomass than treatments that received a single exposure [82]. The efficacy of FC on dewberry control was impacted by both the timing and the frequency of treatments.…”
Section: Hand-held Flame Torchesmentioning
confidence: 99%